Multimodality imaging to identify lipid-rich coronary plaques and predict periprocedural myocardial injury: Association between near-infrared spectroscopy and coronary computed tomography angiography - Ota, Hideaki; Matsuo, Hitoshi; Imai, Shunsuke; Nakashima, Yuki; Kawase, Yoshiaki; Okubo, Munenori; Takahashi, Hiroshi; Kawai, Hideki; Sobue, Yoshihiro; Kawasaki, Masanori; Kondo, Takeshi; Muramatsu, Takashi; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: This study compares the efficacy of coronary computed tomography angiography (CCTA) and near-infrared spectroscopy intravascular ultrasound (NIRS–IVUS) in patients with significant coronary stenosis for predicting periprocedural myocardial injury during percutaneous coronary intervention (PCI). Methods: We prospectively enrolled 107 patients who underwent CCTA before PCI and performed NIRS–IVUS during PCI. Based on the maximal lipid core burden index for any 4-mm longitudinal segments (maxLCBI4mm) in the culprit lesion, we divided the patients into two groups: lipid-rich plaque (LRP) group (maxLCBI4mm ≥ 400; n = 48) and no-LRP group (maxLCBI4mm < 400; n = 59). Periprocedural myocardial injury was a postprocedural cardiac troponin T (cTnT) elevation of 5 times the upper limit of normal. Results: The LRP group had a significantly higher cTnT (p = 0.026), lower CT density (p < 0.001), larger percentage atheroma volume (PAV) by NIRS–IVUS (p = 0.036), and larger remodeling index measured by both CCTA (p = 0.020) and NIRS–IVUS (p < 0.001). A significant negative linear correlation was found between maxLCBI4mm and CT density (rho = −0.552, p < 0.001). Multivariable logistic regression analysis identified maxLCBI4mm (odds ratio [OR]: 1.006, p = 0.003) and PAV (OR: 1.125, p = 0.014) as independent predictors of periprocedural myocardial injury, while CT density was not an independent predictor (OR: 0.991, p = 0.22). Conclusion: CCTA and NIRS–IVUS correlated well to identify LRP in culprit lesions. However, NIRS–IVUS was more competent in predicting the risk of periprocedural myocardial injury.